Performance evaluation of LoraWan physical layer integration on IoT devices - Christos Bouras; Vasileios Kokkinos; Nikolaos Papachristos (Global Information Infrastructure and Networking Symposium (GIIS 2018), Thessaloniki, Greece, 2018)
Due to the constant motion of wireless devices in the Internet of Things (IoT), infrastructure wireless networks cannot provide connectivity at all times, in comparison with ad hoc networks, which are more easy to use and are based on abstract and continuously altering topologies. LoraWan, as a Long Range Wide Area Network specification recommended by the LoRa Alliance, is a low power and long distance communication protocol suitable for IoT environments and applications to different domains such as healthcare and smart farming. This IoT concept is gaining a rapid growth on the IoT market and is simultaneously improving our living environment. In this paper, we first briefly introduce LoRa as an efficient solution of physical layer integration on the IoT devices. We then conduct a performance evaluation taking into consideration metrics such as bit error rate, time on air transmission based on Signal to Noise Ratio (SNR) and Spreading Factors modifications for different bandwidth values.